(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research paper tries to examine the impact of gun violence in the United States of America. The study focused on the recent gun violence in the US schools using guns. The study shows that the every state has studied about carrying guns and it was found that all the states has very similar gun policies yet very different violent crime rates and other variables may be more indicative of violent crime rates. The aim of this paper is to identify topics related to the links among guns, violence and gun control that have not yet been adequately studied, and to very briefly outline the kinds of research that might add useful knowledge about these concerned issues of our modern society. In each section a topic is listed, followed by one or more possible research projects. There is no intention to be exhaustive in coverage. Instead, only the more important issues that have not already been adequately addressed in past researches and those are enlisted and mentioned herein in this research. The research projects are limited (with one exception) to those that are reasonably feasible, and are only broadly outlined, rather than described with the kind of detail that would be provided in a research proposal. Supporting citations have been kept to a minimum to save space interested readers may find relevant information in the pertinent chapters of the book Targeting Guns (Aldine de Gruyter, 1997). The findings also concluded that a majority of individuals that believe that they should be able to maintain the right to protect themselves while carrying concealed weapons.